2022
DOI: 10.1101/2022.10.24.513376
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The nematode effector Mj-NEROSs interacts with ISP influencing plastid ROS production to suppress plant immunity

Abstract: Root-knot nematodes are an important group of plant pathogens that mainly infect plant roots. They establish a feeding site in the host upon infection while secreting hundreds of effectors. These effector proteins are crucial for successful pathogen propagation. Although many effectors have been described, their targets and molecular mode of action are still unknown. Here we report the analysis of the RKN effector, Mj-NEROSs (Meloidogyne javanica nematode effector ROS suppressor), which emerges to have an esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…javanica, NEROS (a homolog of Mi-4D01), also localizes to plastids, where it interacts with host iron-sulphur proteins responsible for electron transfer and ROS production (Stojilković et al, 2023).…”
Section: Role Of Rkn Secretions In Host Redox Manipulationmentioning
confidence: 99%
See 2 more Smart Citations
“…javanica, NEROS (a homolog of Mi-4D01), also localizes to plastids, where it interacts with host iron-sulphur proteins responsible for electron transfer and ROS production (Stojilković et al, 2023).…”
Section: Role Of Rkn Secretions In Host Redox Manipulationmentioning
confidence: 99%
“…RKNs produce and secrete multiple effector proteins, including the transthyretin‐like protein TTL‐5 (Lin et al, 2016), a C‐type lectin (Zhao et al, 2021; Zhuo et al, 2019), protein disulphide isomerase (Tian et al, 2019), Mg16820 (Naalden et al, 2018), and Mj‐NEROS (Stojilković et al, 2023), to counteract the ROS response induced by the host. These effectors are produced in the subventral oesophageal gland cells, which are typically active during early stages of parasitism, and seem to accumulate in or around the migrating nematode as well as in young giant cells (up to ca.…”
Section: Redox Signalling In Plant–rkn Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since chloroplasts and mitochondria play an essential role in plant immunity, different microbial pathogens have been shown to target their effectors to one or both organelles, suppressing plant defense and promoting plant colonization. To date, such pathogens included fungi (Melampsora larici-populina and Rhizoctonia solani), bacteria (Pseudomonas syringae), and nematodes (Meloidogyne javanica), with only two fungus effectors being dualtargeted (Tzelepis et al, 2021;Petre et al, 2015;Stojilković et al, 2022). Very recently, we and others have shown that the coat protein (CP) of melon necrotic spot virus (MNSV) and cucumber necrosis virus (CNV), respectively, are also dual targeted to mitochondria and chloroplasts to attenuate host defense response (Alam et al, 2021;Navarro et al, 2021).…”
Section: )mentioning
confidence: 99%
“…For instance, the hypersensitive response (HR) can be suppressed by targeting a small fungus effector on both organelles (Tzelepis et al, 2021). Besides, the Meloidogyne javanica nematode effector ROS suppressor (Mj-NEROSs) localizes in plastids where it interacts with Iron-Sulfur Proteins (ISP), interfering with the electron transport rate and ROS production (Stojilković et al, 2022).…”
Section: Introductionmentioning
confidence: 99%